Utility of Hounsfield units in predicting fusion rates of patients undergoing anterior odontoid screw fixation following Anderson d'Alonzo type II and shallow type III fractures - Lodin, Jan; Hejčl, Aleš; Bolcha, Martin; Sameš, Martin; Vachata, Petr (Journal of neurosurgical sciences, 2023)
BACKGROUND: Main objective of this study was to determine whether Hounsfield units (HU) measured in three areas of the axis correlate with successful fusion in patients with type II and shallow type III C2 fractures undergoing anterior odontoid screw osteosynthesis (AOSF). METHODS: Forty-five patients with C2 fractures treated via AOSF were analyzed. Only bony fusion with bone trabeculations across the fracture line was considered a successful result. Preoperative HU values were measured in three zones- corpus, watershed and dens. Statistical analysis was performed to determine significant differences between HU of fused and unfused patients in all three zones of a complete and adjusted patient cohort. RESULTS: Statistically significant differences of HU values were found between fused (corpus- 363.7, watershed- 327.9) and unfused (corpus- 279.5, watershed- 194.2) of the complete cohort and the adjusted cohort. Cut-off HU values in the watershed zone were calculated for the complete (250 and 300) and adjusted cohort (240 and 260), dividing patients into three groups of bone quality. Patients with high watershed bone quality (HU>300) achieved successful fusion in 84.62%, patients with low bone quality (HU<250) in 3.85% and patients with medium bone quality (HU 250-300) in 50%. CONCLUSIONS: Preoperative measurement of HU can be used to predict the probability of successful fusion in patients undergoing AOSF for type II and shallow type III C2 fractures. AOSF is a highly effective treatment modality in patients with watershed HU>300, whereas alternatives should be considered in patients with watershed HU<250.
Keywords: kostní šrouby; Spinal Fractures; Fracture Fixation, Internal; dens axis; vnitřní fixace fraktury; Bone Screws; Humans; výsledek terapie; lidé; fraktury páteře; Treatment Outcome; Odontoid Process